SPM Bidang Kesehatan: Kasus Kabupaten Kulon Progo - Kurniawan, Agung (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2002)
The Minimum Service Standard is a benchmark to measure (assess) the performance of the Local Governments in providing the basic services to the public as the obligatory function of the Local Governments. In addition to this standard, Local Governments in fact have been given autonomy to set up their own benchmark to measure the performance of the additional services, which they deliver to thepublic. The Minimum Service Standards should be dynamic and should be reviewed and updated from time to time according to the change of the regional needs and capacities. The dynamic then is reflected in the improvement of the level of performance of the basic services delivered to the public (the minimum service targets), which will be achieved evegyear by the Local Governments. The Minimum Service Standard is different from the Technical Standard In health, for example, the Minimum Service Standard is defined as to provide immunization to 80% of the total children, while the technical standard will specify the number of doses of each antigen, e.g., BCG, OPV, DP7; Measles and Hepatitis, and the ages of the children who should be registered. The Concept of Minimum Service Standard in health for the Local Government of Kulon Progo in this article is defined as how to usefunds obtained from various sources, both from central as well as local, to provide basic health services to thepublic.